Fast and Highly Efficient Adsorption Removal of Toxic Pb(II) by a Reusable Porous Semi-IPN Hydrogel Based on Alginate and Poly(Vinyl Alcohol) - Wang, Wenbo; Liu, Xiangyu; Wang, Xue; Zong, Li; Kang, Yuru; Wang, Aiqin (Frontiers in Chemistry, 2021)
A porous semi-interpenetrating network (semi-IPN) hydrogel adsorbent with excellent adsorption properties and removal efficiency towards Pb(II) were prepared by a facile grafting polymerization reaction in aqueous medium using natural biopolymer sodium alginate (SA) as the main chains, sodium acrylate (NaA) as the monomers, and poly(vinyl alcohol) (PVA) as the semi-IPN component. FTIR, TGA and SEM analyses confirm that NaA monomers were grafted onto the macromolecular chains of SA, and PVA chains were interpenetrated and entangled with the crosslinked network. The incorporation of PVA facilitates to form pores on the surface of hydrogel adsorbent. The semi-IPN hydrogel containing 2 wt.% of PVA exhibits high adsorption capacity and fast adsorption rate for Pb(II). The best adsorption capacity reaches 784.97 mg/g, and the optimal removal rate reaches 98.39% (adsorbent dosage, 2 g/L). In addition, the incorporation of PVA improved the gel strength of hydrogel, and the storage modulus of hydrogel increased by 19.4% after incorporating 2 wt.% of PVA. The increase of gel strength facilitates to improve the reusability of hydrogel. After 5 times of regeneration, the adsorption capacity of SA-g-PNaA decreased by 23.2%, while the adsorption capacity of semi-IPN hydrogel only decreased by 10.8%. The adsorption kinetics of the hydrogel in the initial stage (the moment when the adsorbent contacts solution) and the second stage are fitted by segmentation. It is intriguing that the adsorption kinetics fits well with both pseudo-second-order kinetic model and pseudo-first-order model before 60s, while only fits well with pseudo-second-order adsorption model in the whole adsorption process. The chemical complexing adsorption mainly contribute to the efficient capturing of Pb(II).